Mechanism for efficient photoinduced charge separation at disordered organic heterointerfaces - Eersel, Harm van; Janssen, René A. J.; Kemerink, Martijn (Advanced functional materials, 2012)
Despite the poor screening of the Coulomb potential in organic semiconductors, excitons can dissociate efficiently into free charges at a donor-acceptor heterojunction, leading to application in organic solar cells. A kinetic Monte Carlo model that explains this high efficiency as a two-step process is presented. Driven by the band offset between donor and acceptor, one of the carriers first hops across the interface, forming a charge transfer (CT) complex. Since the electron and hole forming the CT complex have typically not relaxed within the disorder-broadened density of states (DOS), their remaining binding energy can be overcome by further relaxation in the DOS. The model only contains parameters that are determined from independent measurements and predicts dissociation yields in excess of 90% for a prototypical heterojunction. Field, temperature, and band offset dependencies are investigated and found to be in agreement with earlier experiments. Whereas the investigated heterojunctions have substantial energy losses associated with the dissociation process, these results suggest that it is possible to reach high dissociation yields at low energy loss.
Gesehen am 17.12.2019